The Students' Computational Thinking Ability through Problem-Based Learning in Societal Context - Syifa Maharani Priharvian; Ibrahim Ibrahim (Didaktik Matematika, 2024)
The ability to think computationally is a new thing assessed in PISA 2022. In mathematics, Indonesia ranks 70 out of 81 countries with an average score of 366, while the global average is 472. This shows the need for improvement in mathematics learning, one of which is through learning models that support computational thinking skills. This study aims to improve students' computational thinking skills on set material using the Problem-Based Learning model by considering students' prior knowledge. This study used a pseudo-experimental method with a nonequivalent control group design. The study population consisted of 224 grade X students in Bantul High School, and the sample was taken randomly using the cluster random sampling technique, resulting in two classes with a total of 64 students. Data were obtained from pretest and posttest, then analyzed descriptively and with two-way ANOVA and effect size. The results showed that prior knowledge did not significantly affect computational thinking ability. However, the PBL model had a significant moderating effect on students' general computational thinking ability. These results indicate that the problem-based learning model effectively improves these skills.